2020
DOI: 10.1186/s12882-020-02162-4
|View full text |Cite
|
Sign up to set email alerts
|

A mixed-methods feasibility study of an arts-based intervention for patients receiving maintenance haemodialysis

Abstract: Background Haemodialysis can negatively impact quality of life and mental health. Arts-based interventions used successfully in other settings to improve health and well-being, could help address the impact of haemodialysis. This study aimed to evaluate the feasibility and acceptability of conducting a randomised controlled trial (RCT) of an arts-based intervention for patients receiving haemodialysis. Methods A parallel convergent mixed-methods design was used, including a pilot cluster RCT and qualitative p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Qualitative process evaluation. The process evaluation was conducted in parallel to a pilot cluster randomised controlled trial (RCT) that aimed to evaluate the feasibility of evaluating a complex arts-based intervention within the framework of an RCT [12,13].…”
Section: Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Qualitative process evaluation. The process evaluation was conducted in parallel to a pilot cluster randomised controlled trial (RCT) that aimed to evaluate the feasibility of evaluating a complex arts-based intervention within the framework of an RCT [12,13].…”
Section: Designmentioning
confidence: 99%
“…Participants included both patients who had been recruited into a pilot cluster RCT of a complex arts-based intervention [12] and healthcare professionals working on the haemodialysis unit in the UK during the implementation of the intervention. The mean age of participants in the pilot cluster RCT was 69 years, while the mean years participants had been receiving haemodialysis was 4.3 years.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The framework and approach to intervention development promoted acceptability and delivery within both a highly specialised clinical setting and trial framework. The subsequent feasibility study [ 1 ] demonstrated that evaluation of this intervention is feasible within a definitive trial.…”
Section: Key Messages Regarding Feasibilitymentioning
confidence: 99%
“…The initiative builds upon Dr Carswell's PhD study [2,3], which consisted of a pilot feasibility trial of an arts-based intervention for patients receiving haemodialysis. The study aimed to address quality of life and mental health of patients who have end-stage kidney disease (ESKD) and are receiving haemodialysis.…”
mentioning
confidence: 99%